(untitled) (Architecture Image Studies, 2025)
This study analyzes the application of Grice’s maxims in the use of danseigo (male language) and jo-seigo (female language) in the anime Kimi no Na Wa. It focuses on how conversational maxims are fol-lowed or violated and how gendered language influences character interactions. Using a descriptive quali-tative method, 56 dialogues were examined through non-participant observation and recording. Results show that 49 dialogues adhered to the maxims, while 7 violated them, particularly the maxims of quality and relevance. The use of danseigo and joseigo highlights gender traits and interpersonal dynamics among the characters.